Advances in hydroscience. - Yen, Ben Chie, 1935- (Academic Press, 1964)
Advances in Hydroscience, Volume 1 considers the physical theories and mathematical analyses of a broad spectrum of specialized subjects in various branches of hydroscience, including hydrodynamics, hydrology, hydrochemistry, hydrophysics, hydrobiology, hydrometeorology, oceanology, hydrogeology, naval science, and water resources. This book contains five chapters, and begins with a presentation of scientific and engineering advances in the field of sonar and hydroelasticity. The following chapter deals with the fundamental principles and concepts of statistical hydrodynamics in porous media a.